Hormonal Changes Across the Life Cycle of Women and its Effects on the Periodontium - Sourav Chandra Bidyasagar Bal1, Sukhvinder Singh Oberoi2, Radha Prasanna Dalai1, Sashikant Sethy1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In recent years, it has been realized that women’s oral health may differ from that of men in many areas.It is rightly said that the health of a woman’s body and oral cavity are bidirectional, hence women needexceptional dental health facilities and attention. The role that different endocrine hormones imbalancesduring puberty, 1st to 3rd trimester of pregnancy, menopause, oral contraceptive use, and females reproductivecycle details has the main role in various sex data in orofacial health status is supported by different medicalclinical trials. The oral conditions commonly observed during these phases of the lifecycle of femalesinclude inflamed gingiva, the formation of granulomatous tissue in the body, disease of periodontium,, andgrade 1,2,3 mobility of tooth. The closest bonding between status and worst dental health condition in thefemale will need excellent care in investigation plan that assimilates and controls for the diverse array oflurking varying, such as dental diseases (gingivitis, periodontitis and missing tooth), the whole history offemale’s reproductive physiology, and benefaction communal and financial variables. Dental practitionersneed to actively counsel female patients about general and oral health strategies so that they can maintaintheir oral health and maximize their quality of life. The effect of hormonal changes during the life cycle of afemale affects the prevalence and intensity of the oral disease. This understanding is helpful for a clinicianin rendering oral health care to these patients.